Automaticity Revisited: When Print Doesn't Activate Semantics - Labuschagne, Elsa (University of Waterloo, 2014)
It is widely accepted that the presentation of a printed word “automatically” triggers processing that ends with full semantic activation. This processing, among other characteristics, is held to occur without intention, and cannot be stopped. The results of the present experiment show that this account is problematic in the context of a variant of the Stroop paradigm. Subjects named the print colour of words that were either neutral or semantically related to colour. When the letters were all coloured, all spatially cued, and the spaces between letters were filled with characters from the top of the keyboard (i.e., 4, #, 5, %, 6, and *), colour naming yielded a semantically based Stroop effect and a semantically based negative priming effect. In contrast, the same items yielded neither a semantic Stroop effect nor a negative priming effect when a single target letter was uniquely coloured and spatially cued. These findings undermine the widespread view that lexical-semantic activation in word reading is automatic in the sense that it occurs without intention and cannot be derailed.
Keywords: automaticity; semantic Stroop; attention; visual word recognition; Psychology